2005
DOI: 10.1258/002221505775010896
|View full text |Cite
|
Sign up to set email alerts
|

Passive smoking, allergic rhinitis and nasal obstruction in children

Abstract: Allergic rhinitis is a common cause of nasal obstruction in childhood. This prospective study looked at the effect of passive smoking on nasal obstruction in children with and without allergic rhinitis. Eighty-one children took part. Each child was asked to score his or her degree of nasal obstruction on a visual analogue scale. Exposure to passive smoking was determined subjectively using a parental questionnaire, and objectively by measuring the urinary cotinine/creatinine ratio. Results were tabulated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
0
22
0
1
Order By: Relevance
“…Children may inhale SHS through the mouth because of nasal congestion [45], and breastfeeding from a mother who smokes may result in toxic substances being delivered to the child’s mouth [46]. Tobacco smoking was associated with elevated levels of S. mutans and lactobacilli in saliva [47].…”
Section: Resultsmentioning
confidence: 99%
“…Children may inhale SHS through the mouth because of nasal congestion [45], and breastfeeding from a mother who smokes may result in toxic substances being delivered to the child’s mouth [46]. Tobacco smoking was associated with elevated levels of S. mutans and lactobacilli in saliva [47].…”
Section: Resultsmentioning
confidence: 99%
“…• rhinitis 47 and nasal obstruction, 192 • tonsillectomy, adenoidectomy, and placement of pressure-equalizing tubes, 168,179,180,193,194 and…”
Section: Effects On the Child Of Shs Exposurementioning
confidence: 99%
“…However, although we excluded potential confounding factors (craniofacial, neuromuscular, syndromic or defined genetic abnormalities; previous adenoidectomy or sinonasal surgery; upper respiratory tract infection in the previous 14 days; and nasal malformations, polyposis or tumours), as well as children unable to cooperate during the clinical assessment, about 24% of the subjects were allergic and it has been reported that false positive results are significantly more frequent in children with allergies (50% vs. 22.4%, P = 0.009). This suggests that allergies should be considered among the causes of more anterior nasal obstructions that cannot be explained by adenoid size, particularly as it has been reported that nasal obstruction is significantly worse in children with AR than in those without [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, the prevalence of false positive results was significantly higher in children with allergic rhinitis (AR) than in those without allergies, which indicates that AR may be a possible causative factor and therefore needs to be identified in order to stratify patients correctly and plan appropriate treatment. It has been found that nasal obstruction is significantly worse in children with AR than in those without [6], and that its appropriate treatment can prevent the development and reduce the severity [7] of obstructive sleep apnea syndrome, which is frequent in children with enlarged adenoids [8].…”
Section: Introductionmentioning
confidence: 99%